The Conundrum of Calcaneal Spurs: Do They Matter?. Issue 2 (April 2014) - Moroney, Paul J.; O'Neill, Barry J.; Khan-Bhambro, Khalid; O'Flanagan, Shay J.; Keogh, Peter; Kenny, Paddy J.
Background: Chronic plantar heel pain is a common and potentially debilitating condition, often caused by plantar fasciitis. Plantar calcaneal spurs were originally considered the cause of plantar fasciitis but are now regarded as an incidental finding by most authors. We aimed to test this hypothesis and to investigate predisposing factors for the development of spurs.Methods: We reviewed all lateral ankle X rays taken in our institution over a 6-month period and identified all X rays demonstrating calcaneal spurs. Then, we identified a similar number of age- and sex-matched controls without spurs. We contacted both groups by telephone and compared symptoms of heel pain, plantar fasciitis, associated comorbidities, and foot and ankle outcome scores (FAOSs).Results: We reviewed the X rays of 1103 consecutive patients and found a spur prevalence of 12.4%, more common in women and older patients. Questioning of the spur group and control group found a higher body mass index in the spur group. Patients with spurs were 4 times more likely to have diabetes mellitus and 10 times more likely to have lower-limb osteoarthritis. Patients with spurs had more foot pain and poorer FAOS than the control group, even when patients with plantar fasciitis were excluded.Conclusion: Our results demonstrate that the presence of a plantar calcaneal spur may be an indicator of foot pain independent of plantar fasciitis. Although spurs may not cause foot pain themselves, they may be an indication of other associated conditions.Clinical relevance: We have demonstrated the relevance of a radiographic finding once considered irrelevant. Level of Evidence: Prognostic, Level III: Case-control study